2023
DOI: 10.1093/mnras/stad3061
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the jet in M87 revealed by its helical structure imaged with the VLBA at 8 and 15 GHz

A S Nikonov,
Y Y Kovalev,
E V Kravchenko
et al.

Abstract: We present full-track high-resolution radio observations of the jet of the galaxy M87 at 8 and 15 GHz. These observations were taken over three consecutive days in 2009 May using the Very Long Baseline Array (VLBA), one antenna of the Very Large Array (VLA), and the Effelsberg 100 m telescope. Our produced images have dynamic ranges exceeding 20 000:1 and resolve linear scales down to approximately 100 Schwarzschild radii, revealing a limb-brightened jet and a faint, steep spectrum counter-jet. We performed je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…On (sub)parsec scales, recent studies of M87 have also reported quasiperiodic sideways motion of the inner structure based on long-term monitoring observations (Britzen et al 2017;Walker et al 2018;Ro et al 2023). In addition, high-dynamic range Very Long Baseline Array observations have revealed three helical threads inside the jet (Nikonov et al 2023). It seems likely that these phenomena are related to the propagation of jet instabilities, such as Kelvin-Helmholtz instability (KHI) or current-driven kink ones, and/or caused by perturbed mass injection into the jet.…”
Section: Introductionmentioning
confidence: 99%
“…On (sub)parsec scales, recent studies of M87 have also reported quasiperiodic sideways motion of the inner structure based on long-term monitoring observations (Britzen et al 2017;Walker et al 2018;Ro et al 2023). In addition, high-dynamic range Very Long Baseline Array observations have revealed three helical threads inside the jet (Nikonov et al 2023). It seems likely that these phenomena are related to the propagation of jet instabilities, such as Kelvin-Helmholtz instability (KHI) or current-driven kink ones, and/or caused by perturbed mass injection into the jet.…”
Section: Introductionmentioning
confidence: 99%